Comparison of immediate versus delayed frozen embryo transfer on reproductive outcome - Arzu Yurci; Aret Kamar; Nurettin Turktekin; Ramazan Ozyurt (IMR Press, 2021)
The aim of this study was to compare impact of immediate versus delayed frozen frozen embryo transfer on reproductive outcome in patients undergoing IVF treatment. A total of 1478 infertile women with frozen embryos, aged between 18-42 years, were included the study. Patients were divided into two groups according to the time of embryo transfer. All transfers done in the first cycle after egg retrieval were deemed "immediate frozen ET" and a transfer done in any subsequent cycle was deemed "delayed frozen ET". The effects of immediate versus delayed FET on beta-hCG positivity, clinical pregnancy rate (CPR), ongoing pregnancy rate (OPR), live birth rate (LBR) and miscarriage rate were compared. Multiple logistic regression analysis was performed to exclude possible factors affecting reproductive parameters. Beta-hCG positivity, the number of patients with gestational sac and clinical pregnancy rates were found to be similar in both groups. The miscarriage rates in the Delayed FET group were found to be higher than the immediate FET group. Therefore, OPR was higher in the immeadiate FET group. When compared to the Delayed FET group, LBR was recorded as 1.3 times higher in the immediate FET group. When the cases with embryo transfer on the fifth or sixth day were compared with the cases with embryo transfer on the 3rd or 4th day, a 2.1 fold increase in LBR was found in the immediate FET group compared to the delayed FET group. Immediate FET done in the first cycle after egg retrieval increases the live birth rates while decreasing the abortion rates.